Difference in Activity in the Supplementary Motor Area Depending on Limb Combination of Hand–Foot Coordinated Movements - Nakagawa, Kento; Kawashima, Saeko; Mizuguchi, Nobuaki; Kanosue, Kazuyuki (Frontiers in Human Neuroscience, 2016)
Periodic interlimb coordination shows lower performance when the ipsilateral hand and foot (e.g. right hand and right foot) are simultaneously moved than when the contralateral hand and foot (e.g. right hand and left foot) are simultaneously moved. The present study aimed to investigate how brain activity that is related to the dependence of hand-foot coordination on limb combination, using functional magnetic imaging (fMRI). Twenty-one right-handed subjects performed periodic coordinated movements of the ipsilateral or contralateral hand and foot in the same or opposite direction in the sagittal plane. Kinematic data showed that performance was lower for the ipsilateral hand-foot coordination than for the contralateral one. A comparison of brain activity between the same and opposite directions showed that there was a greater activation of supplemental motor area (SMA) for ipsilateral hand-foot coordination as compared to that seen during contralateral hand-foot coordination. We speculate that this might reflect a difference in the degree of inhibition of the neural circuit that disrupts opposite directional movements between ipsilateral and contralateral hand-foot coordinated movements.